Deficiency of PPARalpha disturbs the response of lipogenic flux and of lipogenic and cholesterogenic gene expression to dietary cholesterol in mouse white adipose tissue. - Islam, K; Knight, B; Frayn, K; Patel, D; Gibbons, G (2005)
PPARalpha-deficiency in mice fed a high-carbohydrate, low-cholesterol diet was associated with a decreased weight of epididymal adipose tissue and an increased concentration of adipose tissue cholesterol. Consumption of a high (2% w/w) cholesterol diet resulted in a further increase in the concentration of cholesterol and a further decrease in epididymal fat pad weight in PPARalpha-null mice, but had no effect in the wild-type. These reductions in fat pad weight were associated with an increase in hepatic triacylglycerol content, indicating that both PPARalpha-deficiency and cholesterol altered the distribution of triacylglycerol in the body. Adipose tissue de novo lipogenesis was increased in PPARalpha-null mice and was further enhanced when they were fed a cholesterol-rich diet; no such effect was observed in the wild-type mice. The increased lipogenesis in the chow-fed PPARalpha-null mice was accompanied paradoxically by lower mRNA expression of SREBP-1c and its target genes, acetyl-CoA carboxylase and fatty acid synthase. Consumption of a high-cholesterol diet increased the mRNA expression of these genes in the PPARalpha-deficient mice but not in the wild-type. De novo cholesterol synthesis was not detectable in the adipose tissue of either genotype despite a relatively high expression of the mRNA's encoding SREBP-2 and 3-hydroxy-3-methylglutaryl Coenzyme A reductase. The mRNA expression of these genes and of the LDL-receptor in adipose tissue of the PPARalpha-deficient mice was lower than that of the wild-type and was not downregulated by cholesterol feeding. The results suggest that PPARalpha plays a role in adipose tissue cholesterol and triacylglycerol homeostasis and prevents cholesterol-mediated changes in de novo lipogenesis.